2009
DOI: 10.1103/physrevb.79.073412
|View full text |Cite
|
Sign up to set email alerts
|

Localized surface-plasmon resonances in periodic nondiffracting metallic nanoparticle and nanohole arrays

Abstract: We compare the optical response of periodic nondiffracting metallic nanoparticle and nanohole arrays. Experimental data from both structures show a pronounced minimum in their wavelength-dependent transmittance that, through numerical modeling, we identify as being due to the excitation of localized surface-plasmon resonances associated with the nanoparticles/nanoholes. Our main finding is that, while the optical response of the nanoparticle arrays is largely independent of interparticle separation, the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 27 publications
8
81
0
1
Order By: Relevance
“…Resonant absorption of light in the hole arrays results from the diffractive coupling of incident light to surface plasmon polaritons (SPP) propagating at the metal-dielectric interface (12,31). For the thin (18 nm) Au films used, SPPs on the Au-air and the Auglass interface are strongly coupled (32), giving rise to symmetric and anti-symmetric insulator-metal-insulator (IMI) SPP modes.…”
Section: S9 Mechanism Of Resonant Absorption In Hole Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Resonant absorption of light in the hole arrays results from the diffractive coupling of incident light to surface plasmon polaritons (SPP) propagating at the metal-dielectric interface (12,31). For the thin (18 nm) Au films used, SPPs on the Au-air and the Auglass interface are strongly coupled (32), giving rise to symmetric and anti-symmetric insulator-metal-insulator (IMI) SPP modes.…”
Section: S9 Mechanism Of Resonant Absorption In Hole Arraysmentioning
confidence: 99%
“…Due to the strong dispersion, the array pitches required to couple to the IMI SPP are much smaller than the free-space wavelength (e.g. 200 nm at = 600 nm) (31).…”
Section: S9 Mechanism Of Resonant Absorption In Hole Arraysmentioning
confidence: 99%
“…Instead of antennae one can also design metamaterials based on inverse structures, i.e. sub--wavelength apertures in a metallic sheet [19][20][21] and utilise Babinet's principle 22,23 or extraordinary transmission 24 based on surface--plasmon excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Using such nanohole arrays etched into a gold metallic film, it has been shown that the LSPR can be easily tuned through the visible and NIR region of the electromagnetic spectrum simply by altering the interhole separation distance. 110,108 This tunability for a particular application of interest allows for dramatic increases in SPR sensitivity. 107,[118][119][120] Although the tunability of such nanoarrays in gold is limited to the NIR and longer wavelength region of the visible (i.e., ∼500 nm or greater), a variation of these nanoslit and nanohole arrays, known as nanotriangle arrays [see Fig.…”
Section: Recent Advances In Surface Plasmonmentioning
confidence: 99%